2011
DOI: 10.1002/jmv.22156
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Detection of rotavirus RNA in the cerebrospinal fluid of a child with rotavirus gastroenteritis and meningism

Abstract: Although case reports have described detection of rotavirus (RV) in extraintestinal sites such as the liver, kidney, and central nervous system (CNS) of children with RV gastroenteritis, CNS localization in RV infection seems to be rare. RT‐PCR and nucleotide sequencing detected a G1P[8] strain in the stool and cerebrospinal fluid (CSF) samples of a patient with concurrent RV‐associated enteritis and CNS signs. Upon sequence analysis, the viruses detected in the CSF was identical to the virus detected in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Moreover, in this study, some infants presented convulsions, for which aseptic meningitis cannot be excluded (Tang et al, 2010). The existence of RV in the cerebrospinal fluid in infants with RV enteritis complicated by meningitis suggests that RV can lead to viremia (Medici et al, 2011), which can lead to CNS damage (Kawano et al, 2007). However, it has been suggested that both RV-caused viremia and brain damage lack a reliable theoretical basis (Fang, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in this study, some infants presented convulsions, for which aseptic meningitis cannot be excluded (Tang et al, 2010). The existence of RV in the cerebrospinal fluid in infants with RV enteritis complicated by meningitis suggests that RV can lead to viremia (Medici et al, 2011), which can lead to CNS damage (Kawano et al, 2007). However, it has been suggested that both RV-caused viremia and brain damage lack a reliable theoretical basis (Fang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…All children were confirmed to have RV infection and met the diagnostic criteria of RV enteritis (Medici et al, 2011). They were all confirmed to have no histories of congenital heart disease, myocarditis, toxic encephalopathy, hepatorenal diseases, and various muscle diseases.…”
Section: Subjectsmentioning
confidence: 99%
“…The majority of the intestinal epithelium is a collection of T lymphocytes in lymph nodes; thus, investigating the role of antiviral cell-mediated immunity in the gut is particularly important (4). With the increasing number of studies investigating the abnormal immune response and the mechanism underlying RV infection in the body, a variety of cellular immune responses associated with RV cells and cytokines have been demonstrated to be involved in the inflammatory response (5,6). An imbalance in the proportion of regulatory T cells (Treg)/T helper 17 cells (Th17), and the subsequent expression of cytokines, has become the theoretical basis for the study of various autoimmune disorders and other diseases (7)(8)(9).…”
Section: Rotavirus (Rv) Infection Is a Common Disease Worldwidementioning
confidence: 99%
“…In one study, RV antigen was diagnosed in 30 of 70 serum samples, and levels of antigen in the sera were significantly increased at the acute phase of the RV infections [21]. Acute sera from children with RV associated encephalopathy were identified to be positive with RV antigen, demonstrating antigenemia; however, the antigen was not detected in the cerebro-spinal fluid [39]. Most of the findings concerning antigenemia were observed during the early phase of infection, where the RV antigen levels in the sera peaked at 2 days post-inoculation (dpi), and no antigen was detected at 6 dpi [48,56].…”
Section: Extra-intestinal Spread Of Rotavirus Infection In Childrenmentioning
confidence: 99%
“…It may seem that RV can move to these organs via viremia, but there is still no indication whether it can replicate efficiently outside the intestine. Increasing reports presented detection of RV antigen or RNA in the cerebrospinal fluid of diarrheic children [23,30,37,39,45]. Previously, reported cases showed the presence of RV nucleic acid in cerebrospinal fluid of children with acute cerebellitis which was attributed to cerebellar seizures [14,47].…”
Section: Extra-intestinal Spread Of Rotavirus Infection In Childrenmentioning
confidence: 99%